Blood Biochemical Dynamics and Correlations in Laying Hens after Experimental Nickel Administration - Capcarova, Marcela; Kolesarova, A.; Arpasova, H.; Massanyi, P.; Lukac, N.; Kovacik, J.; Kalafova, A.; Schneidgenova, M. (International Journal of Poultry Science, 2008)
The concentrations of biochemical parameters (calcium, phosphorus, magnesium, sodium, potassium, glucose, total cholesterol, total proteins, triglycerides, alanine aminotransferase ALT, aspartate aminotransferase AST, gamma glutamyl transferase GGT and glutamatdehydrogenase GLDH) and their correlations in blood serum of Isa brown breed of laying hens after nickel administration were analyzed. Animals were divided into four groups (K, P1, P2, P3). Experimental hens (5 in each group) received nickel (NiCl2) per os in drinking water in various dose (P1 - 20 mg NiCl2/L; P2 - 200 mg NiCl2/L; P3 - 2000 mg NiCl2/L of drinking water) for 28 days, control group - K (n=5) did not receive nickel during experiment. Blood collection was realized at Day 0 (collection - control), Day 7 (collection 1), Day 14 (collection 2), Day 21 (collection 3) and Day 28 (collection 4). Significant decreases (P<0.05) of magnesium and triglyceride between control (1.74±0.28 mmol/L and 20.92±8.13 mmol/L) and P3 group (0.91±0.37 mmol/L and 8.04±8.49 mmol/L) were found. Nickel had only slight effect on other parameters of energy, enzymatic and mineral profile as the results were not significant. Positive high correlation between Ca-ALT (r = 0.71), P-ALT (r = 0.74) and total proteins (TP) -ALT (r = 0.77) in the control group was detected. Negative high correlation between P-K (r = -0.75) and Mg-K (r = -0.73) in group P1 and positive high correlation between P-cholesterol (r = 0.74), Na-ALT (r = 0.69) and cholesterol-triglycerides (TG) (r = 0.87) in group P1 was noted. Positive high correlation between Ca-ALT (r = 0.71) and cholesterol-TG (r = 0.91) in the group P2 and positive high correlation in P3 group was found: Ca-TG (r = 0.69), Mg-TG (r = 0.67), Na-AST (r = 0.69) and glucose-AST (r=0.71).